2024
DOI: 10.1021/acs.jmedchem.3c01719
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Effective Dual PROTAC Degraders for Neurodegenerative Disease-Associated Aggregates

Wentao Zhu,
Wenqian Zhang,
Jian Chen
et al.

Abstract: The aggregation of specific proteins is a histopathological hallmark in various neurodegenerative diseases (NDs), among which Alpha-synuclein (α-Syn) and tau have received increased attention. The targeted protein degradation (TPD) strategy has been studied in the treatment of NDs, but multitarget bifunctional molecules have been ignored. Herein, a series of effective dual PROTAC degraders were developed, which could degrade α-Syn aggregates and total tau simultaneously. The degradation effects were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Targeted protein degradation (TDP) technologies include proteolysis-targeting chimeras (PROTACs), autophagy-targeting chimeras (AUTACs), and autophagosome-anchoring chimeras (ATACCs). Although the application of TDP technologies for NDs is still in its infancy, recent studies have shown that their use is a strategy worth exploring [ 299 , 300 ]. The combination of TDP technologies with multitarget strategies is also a direction that can be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted protein degradation (TDP) technologies include proteolysis-targeting chimeras (PROTACs), autophagy-targeting chimeras (AUTACs), and autophagosome-anchoring chimeras (ATACCs). Although the application of TDP technologies for NDs is still in its infancy, recent studies have shown that their use is a strategy worth exploring [ 299 , 300 ]. The combination of TDP technologies with multitarget strategies is also a direction that can be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic development for CNS diseases is challenging due to blood brain barrier (BBB) permeability constraints, and in the druggability of protein aggregates which often characterize neurodegenerative pathologies. Commonly used degrader approaches have the potential to target proteins or aggregated complexes for degradation by the ubiquitin-proteasome (UPS) system ( Bekes et al, 2022 ; Zhu et al, 2024 ) or autophagy-lysosome machinery ( Pei et al, 2021 ; Ji et al, 2022 ). Targeted protein degraders act through event-driven pharmacology via non-reversible removal of functional components, and their potency is boosted by a catalytic mode of action (MOA), enabling sub-stoichiometric dosing regimens ( Bekes et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%